2022
DOI: 10.1186/s12887-022-03509-6
|View full text |Cite|
|
Sign up to set email alerts
|

Acute pancreatitis in 60 Iranian children: do pediatricians follow the new guidelines in diagnosis and management of acute pancreatitis?

Abstract: Background The incidence of acute pancreatitis in children is increasing, but causes and diagnostic and therapeutic methods are various in different centers. The aim of this study was to investigate the common causes and routine diagnostic and therapeutic methods of acute pancreatitis in children in a pediatric gastrointestinal referral center and its accordance with existing guidelines. Methods In this retrospective, cross-sectional study, a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error in two of the author names: the letter ‘i’ at the end of the names of "Hosein AliMadadi" and "Mohammad Hassan Sehouli" had been mistakenly removed, and the Acknowledgements declaration had been incorrectly written (namely, the department that Dr Pejman Rohani heads had been incorrectly written).…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in two of the author names: the letter ‘i’ at the end of the names of "Hosein AliMadadi" and "Mohammad Hassan Sehouli" had been mistakenly removed, and the Acknowledgements declaration had been incorrectly written (namely, the department that Dr Pejman Rohani heads had been incorrectly written).…”
mentioning
confidence: 99%